Identifikasi Bakteri Escherichia Coli Pada Sisa Parutan Kelapa Yang Ada Pada Mesin Parut Di Pasar Hartaco Makassar - Andi Indrawati (Prodi D-III Analis Kesehatan niversitas Indonesia Timur, 2016)
This research was motivated by the process along with the grated coconut development times are also becoming more sophisticated. The emergence of various kinds of machines with a variety of different brands and types help people to do the grater which only requires a relatively short time. Given the lack of information about the technology pemarutan coconut hygiene and sanitation equipment used and the washing process coconut less attention in Makassar Hartaco market that can cause various diseases, one of which is diarrhea. Of 5 samples tested research using selective medium (Endo Agar). Medium differentiation (KIA), Medium biochemical (IMVIC), and medium confectionery, result/ data as much as 5 samples are negative which means there are Escherichia coli in the rest of the grated coconut. Based on the research results suggested to employers grated coconut grated coconut before should pay attention to hygiene equipment and water used must be clean running water for washing and coconut